European Green Deal: Study of the Combined Agricultural Aggregate. - Nadykto, Volodymyr; Надикто, Володимир Трохимович; Kyurchev, Volodymyr; Кюрчев, Володимир Миколайович; Findura, Pavol; Hutsol, Taras; Kurpaska, Sławomir; Krakowiak-Bal, Anna; Vasyuk, Vyacheslav (My University, 2023)
ENG :The modern world industry involves the use of innovative approaches and optimisations of the existing agricultural management methods, which contribute to the implementation of the sustainable development of related industries and economies of different countries. The use of mobile agricultural units with extended functional properties can have a steady demand in the agricultural machinery market and contribute to the practical implementation of the philosophy of the “European Green Deal”. The research results show that when assembling a unit for mowing agricultural crops with simultaneous grinding and placing their stubble in the soil, preference should be given to a self-propelled machine with rear swivel wheels. When using a wheeled tractor, it must have a reversible control post and a reversible transmission. A mathematical model of the collecting unit was developed, which allows for obtaining the corresponding amplitude and phase frequency characteristics and, with their help, the stability of the horizontal movement was evaluated. According to the results of field studies, the dispersion of the angle of directional oscillation of the tractor with front-steered wheels was 4.48 grad2. For the tractor with rear-steered wheels, the value of this statistical parameter was 2.90 grad2, which, according to the F-test at the level of statistical significance of 0.05, is naturally lower.///////////// UKR : Сучасна світова промисловість передбачає використання інноваційних підходів та оптимізацію існуючих методів ведення сільського господарства, які сприяють реалізації сталого розвитку суміжних галузей та економік різних країн. Використання мобільних сільськогосподарських агрегатів з розширеними функціональними властивостями може мати стійкий попит на ринку сільськогосподарської техніки та сприяти практичній реалізації філософії «Європейської зеленої угоди». Результати досліджень показують, що при складанні агрегату для скошування сільськогосподарських культур з одночасним подрібненням і закладенням їх стерні в ґрунт перевагу слід надавати самохідній машині із задніми поворотними колесами. При використанні колісного трактора він повинен мати реверсивний пост управління і реверсивну передачу. Розроблено математичну модель збирального вузла, яка дозволяє отримати відповідні амплітудно-фазочастотні характеристики та з їх допомогою оцінено стійкість горизонтального руху. За результатами натурних досліджень дисперсія кута направлених коливань трактора з передньокерованими колесами склала 4,48 град 2 . Для трактора із задньокерованими колесами значення цього статистичного параметра становило 2,90 град 2 , що за F-критерієм на рівні статистичної значущості 0,05 закономірно є нижчим.
Європейська зелена угода: дослідження комбінованого сільськогосподарського агрегату.
Keywords: amplitude frequency characteristic (AFC); disc harrow; European Green Deal; sustainable; header; phase frequency characteristic (PFC); амплітудно-частотна характеристика; стійкий; Європейська зелена угода; фазочастотна характеристика (ФЧХ); дискова борона